Extended-Spectrum Beta-Lactamase Enzyme (ESBL) Production from Antimicrobial-Resistant Escherichia coli Isolates and their Attachment on Stainless-Steel Surface - S, Isa; Syifaâ€™ J., Nur; R.N, Fathurrahman; M.A.R, Nor-Khaizura; N.A, Mahyudin (International Journal of Engineering and Technology, 2019)
Food contact surfaces may pose a threat of becoming vector for antimicrobial-resistant transmission of bacteria along the food chain. Twenty-four isolates of Escherichia coli were investigated to determine the antimicrobial resistance, production of Extended-Spectrum Beta-Lactamase Enzyme and their attachment ability on stainless-steel surface. The antimicrobial resistance and enzyme production tests were carried out according to standard disc diffusion assay, while attachment was simulated on stainless steel discs. All 24 isolates were resistant to Amoxycillin and Penicillin, while 50% and 37.5% were resistant to Ceftriaxone and Cefotaxime, respectively. Three of 24 isolates (12.5%) produced the enzyme against cefotaxime, ceftazidime and ceftriaxone. The enzyme production was further confirmed by the expansion of cefotaxime, ceftriaxone and ceftazidime inhibition zone towards amoxicillin-clavulanate disc. All 3 enzyme-producing isolates (EC-6, EC-7 and EC-12) exhibited their ability to attach to stainless-steel disc. Attachment was significantly increased (p<0.05) with prolonged incubation times with the highest attachment (6.07Â±0.05 log10 cfu/ml) by isolate EC-6 at 72h. The attachment ability indicates that resistant E. coli can be potentially transmitted into the food chain via contaminated food contact surfaces. Our data could be used to develop research to link the spread of antimicrobial resistance towards effective intervention strategies.Â Â